농촌경관 관리 및 지원 시범사업에 대한 성과 분석 및 개선 방안 도출 연구 - 성주인 (한국농촌경제연구원, 2007)
Recently the management of rural landscape attracts many interests. The Direct Payment program for rural landscape conservation has been practiced by MAF(ministry of agriculture and forest) since 2005. This program is the only measure for rural landscape conservation. This study, thus, evaluates the effects of the Direct Payment program for rural landscape conservation and proposes the improvement measures to the program. For that, we firstly examined the present condition of the Direct Payment program for rural landscape conservation. Secondly, we specified the effect factors of the Direct Payment program for rural landscape conservation based on the literature review and evaluated the effects. At this time, we implemented a questionnaire survey and interviewed local government officers, the residents of target villages, and general farmers. The survey, which became a basis for the evaluation of the effects, consists of two groups: one with a group of 150 people who live in the target villages, and the other with a group of 600 people who are the general farmers nationwide. Thirdly, we examined the issues of the Direct Payment program for rural landscape conservation as following: 1) the amount of a subsidy, 2) the plant species, 3) target size, 4) application process, and so on. Lastly, we made the suggestions for improving the Direct Payment program for rural landscape conservation and the policy measures for management of rural landscape. The Direct Payment program for rural landscape conservation gets the considerable results. Especially, the target villages have had many visitors through the formation of the good landscape. Moreover, the community consciousness of the target village residents becomes higher. But it is the limitation that the target village residents seldom act in order to manage the rural landscape except the cultivation of landscape plants. Finally, it is necessary to induce regional governments to participate in rural landscape conservation programs and to differentiate the landscape management policies considering regional characteristics. In the short term, the Direct Payment program for rural landscape conservation should be enlarged through improving the problems. And in the long term, it is important to provide the target village residents with incentives in order to act voluntarily for the rural landscape management. Researchers: Joo-In Seong and Ju-Young Park E-mail: jiseong@krei.re.kr